Peer feedback on video consultations for GPST1s in S.E. Scotland: a pilot study using the Framework Method. Issue 6 (2nd November 2021) - Phillips, Rachel; Allbutt, Helen
ABSTRACT: Introduction : Our study explored the educational value and feasibility of small-group peer feedback on video consultations for early-stage GP trainees facilitated by a near-peer. Methods: Ten GP trainees in their first placement shared videos of patient consultations requiring improvement in small groups facilitated by a near-peer using the ALOBA feedback format. Trainees and the facilitator were interviewed by a social scientist immediately post-intervention and asked for written email reflection some weeks later. Analysis of observations, interviews and feedback followed the Framework Method. Results: Six themes incorporated both assumed and unanticipated processes and outcomes. Receipt and production of peer feedback were seen to prompt critical analysis and led to processing of previously received supervisor feedback. Trainees valued the ability to benchmark against peers at the same stage of training. The small groups conferred social support and the opportunity to calibrate complex mental health judgements inherent to primary care with each other and a near-peer. Conclusions: GP trainees can engage with and benefit from structured small-group peer feedback early in training. Sessions offered educational value over and above supervisor feedback, especially for trainees inclined to be anxious and self-critical.